Impact of life-threatening military incidents during deployments abroad on the relationships between military personnel and their families - Wesemann, Ulrich; Rowlands, Katie; Renner, Karl-Heinz; Konhäuser, Lucas; Köhler, Kai; Himmerich, Hubertus (Frontiers in Psychiatry, 2024)
Introduction The influence of deployments on family relationships has hardly been investigated. Following a recently proposed new research strategy, military personnel with and without deployment-related life-threatening military incidents during deployment were compared. The hypothesis was that partner and family relationships of military personnel who experienced such an event would deteriorate more. Methods This study included N = 255 military personnel who had a romantic partner (n = 78 of them had children) when deployed to Afghanistan. Of these, n = 68 military personnel experienced a deployment-related critical event during the deployment, n = 187 did not. Partnership quality was assessed using a semi-structured pre- and post-deployment interview. Results The partner relationships of military personnel who experienced a deployment-related life-threatening military incident during deployment broke up significantly more often. The partner relationships of all military personnel deteriorated significantly, with greater deterioration after deployment in the group who faced such incidents. These results were independent of age, rank or number of previous deployments. In addition, there was a significant deterioration in the relationships between all military personnel and their children with greater deterioration after deployment in the group who faced such incidents. Conclusion Life-threatening military incidents during a deployment abroad appear to have a considerable influence on the quality and stability of the partner and family relationships of military personnel. These findings can be used to inform the development of specific pre- and post-deployment measures and training.